Deductive verification of requirements for event-driven architecture - Letichevsky, A.; Letychevskyi, О.; Peschanenko, V.; Guba, A. (Проблеми програмування, 2013)
The current paper presents the technology of processing of requirements for systems with event-driven architecture. The technology consists of the stages of formalization, formal verification and conversion to design specifications. The formalization is the formal description of events as formal specifications called basic protocols. The consistency and completeness of basic protocols, safety properties and user-defined properties are verified. The deductive tools for dynamic and static checking are used for detection of properties violation. The method of enlargement allows reducing the complexity of proving and solving. Formal presentation of requirements allows converting them to SDL\UML specifications and generating the test suite. The technology is realized in IMS system and applied in more than 50 projects of telecommunication, networking, microprocessing and automotive systems.